2019
DOI: 10.1371/journal.ppat.1007772
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing antibodies from an individual that naturally cleared multiple hepatitis C virus infections uncover molecular determinants for E2 targeting and vaccine design

Abstract: Cumulative evidence supports a role for neutralizing antibodies contributing to spontaneous viral clearance during acute hepatitis C virus (HCV) infection. Information on the timing and specificity of the B cell response associated with clearance is crucial to inform vaccine design. From an individual who cleared three sequential HCV infections with genotypes 1b, 1a and 3a strains, respectively, we employed peripheral B cells to isolate and characterize neutralizing human monoclonal antibodies (HMAbs) to HCV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 66 publications
(114 reference statements)
1
51
0
Order By: Relevance
“…While in this work we report systematic computational alanine scanning to identify key energetic determinants of a large set of monoclonal antibodies that target the SARS-CoV-2, other studies have reported experimental global alanine scanning of antibody interactions with viral glycoproteins, such as hepatitis C virus E1E2, to map binding determinants (Colbert et al, 2019;Gopal et al, 2017;Keck et al, 2019;Pierce et al, 2016). These datasets were used to cluster antibodies and E1E2 positions by binding profiles in several of those studies (Colbert et al, 2019;Keck et al, 2019;Pierce et al, 2016). Though based on deep mutational scanning rather than direct measurement of binding affinities, recent studies provide information on the impact of RBD substitutions to alanine and other residues on recognition by sets of monoclonal antibodies (Greaney et al, 2021b;Starr et al, 2021), and such data could be inspected with respect to residue and mutation-level impact on antibody clusters identified here.…”
Section: Discussionmentioning
confidence: 99%
“…While in this work we report systematic computational alanine scanning to identify key energetic determinants of a large set of monoclonal antibodies that target the SARS-CoV-2, other studies have reported experimental global alanine scanning of antibody interactions with viral glycoproteins, such as hepatitis C virus E1E2, to map binding determinants (Colbert et al, 2019;Gopal et al, 2017;Keck et al, 2019;Pierce et al, 2016). These datasets were used to cluster antibodies and E1E2 positions by binding profiles in several of those studies (Colbert et al, 2019;Keck et al, 2019;Pierce et al, 2016). Though based on deep mutational scanning rather than direct measurement of binding affinities, recent studies provide information on the impact of RBD substitutions to alanine and other residues on recognition by sets of monoclonal antibodies (Greaney et al, 2021b;Starr et al, 2021), and such data could be inspected with respect to residue and mutation-level impact on antibody clusters identified here.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Clearance of HCV infection therefore requires a robust and cross-reactive CD4 and CD8 T-cell response as well as neutralizing antibodies. 49,50 Identification and characterization of cytotoxic T lymphocytes (CTL) epitopes as well as broadly neutralizing antibodies that target conserved epitopes of the E1 and E2 glycoproteins on the viral surface has prompted the exploration of peptide-based vaccine strategies. 51 IC41 is a vaccine candidate that consists of five synthetic peptides (IPEP 83, 84, 87, 89, and 1426) from core, NS3, and NS4 proteins harboring HCV CD4 and CD8 T-cell epitopes along with the synthetic adjuvant poly-L-arginine.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…A vaccine capable of preventing chronic infection would significantly expedite current elimination programmes; consequently, there is renewed interest in determining the immune-correlates of viral clearance and developing immunogens capable of eliciting such responses [1]. These efforts have accumulated evidence that neutralising antibody responses targeting the major HCV glycoprotein, E2, protect individuals from chronic infection, thus placing E2 at the forefront of current HCV vaccine development [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%